Effect of Gym and Home-based Combined Training on Indicators of Central Obesity and Quality of Life in Men with Primary Hypertension - Fatemeh Islami; Marziyeh Saghebjoo; Toba Kazemi (Mazandaran University of Medical Sciences, 2023)
Introduction and purpose: Regular training improves cardiovascular diseases. However, performing home-based exercise and determining its benefits have been less inves tigated in patients with cardiovascular diseases. The present s tudy aimed to inves tigate the effect of 10 weeks of the gym and home-based combined training (GBCT and HBCT respectively) on indicators of central obesity and quality of life in men with primary hypertension. Methods: Forty-six patients (48 ± 9 years) were randomly selected and assigned into three groups; GBCT (n = 16), HBCT (n = 15), and control (n = 15) group. The combined training program included resis tance, aerobic and s tretching exercises. Body composition was measured, central obesity indices were calculated and selected ques tionnaires were completed by all participants before and after the intervention. The data were analyzed using appropriate s tatis tical tes ts at a significance level of P ≤ 0.05. Results: Tri-ponderal mass index significantly decreased after GBCT and HBCT compared to that of the control group. The hip index decreased significantly after HBCT compared to that of the control group. Also, the body shape index and conicity index significantly decreased in the GBCT group compared to those in the HBCT group. Furthermore, the mean of the body adiposity index significantly decreased in GBCT and HBCT groups and the weight-adjus ted-wais t index significantly increased in the HBCT group. The quality of life and its different dimensions remained unchanged after the intervention. Conclusion: GBCT and HBCT improve some indicators of central obesity; therefore, implementation of home-based exercise is sugges ted for cardiovascular patients.